Características estruturais e propriedades mecânicas de fios ortodônticos de níquel-titânio - Ana Cristina Rodrigues Antunes de Souza (2006)
The purpose of this study was to evaluate and to compare the thermomechanical properties of three distinct rectangular orthodontic NiTi wires by means of structural caracterization, torsion and tensile tests. In addition, the martensitic and reverse transformation temperatures were compared to straight, bent and cycled torsion wires.Two NiTi wires were composed by equiatomic Ni and Ti and another one wire composed by Ni, Ti and Cu. At room temperature, the austenitic was the main phase presented in all wires. Roughness surface and finishing irregularities were observed in all wires. The Af temperatures of bending wires were increased as compared to straight ones. The torsional behavior and transformation temperatures of straight wires revealedits properties. The Superelastic wires showed NiTi martensitic behavior under torsion tests and probably in clinical use, due to the high Af and Mf temperatures exhibited. The Shape memory wires showed superelastic and shape memory properties. The multistranded wires showed superelastic behavior. The cycling torsion test did not exhibit influence on the mechanical properties of the wires. By the way, the tensile results were in according to the torsion findings.